91.1k views
2 votes
0.6(x + 2) = 0.55(2x + 3)

1 Answer

2 votes

Answer:

-0.9

Explanation:

0.6(x+2)=0.55(2x+3)

Use the distributive property to multiply 0.6 by x+2.

0.6x+1.2=0.55(2x+3)

Use the distributive property to multiply 0.55 by 2x+3.

0.6x+1.2=1.1x+1.65

Subtract 1.1x from both sides.

0.6x+1.2−1.1x=1.65

Combine 0.6x and −1.1x to get −0.5x.

−0.5x+1.2=1.65

Subtract 1.2 from both sides.

−0.5x=1.65−1.2

Subtract 1.2 from 1.65 to get 0.45.

−0.5x=0.45

Divide both sides by −0.5.

x= 0.45/−0.5

x= -0.9

xoxo,

your highness...

User Nithya Rajan
by
4.4k points